The Framework of Paradox at Ala-Muntami Discourse in “Alqundus – The Beaver” a Novel by Mohammad Hasan Alwan - Al-Zahrani, Amirah Ali Abdullah (Journal of Arabic Language Sciences and Literature, 2022)
The study examines the framework of paradox in the Ala-Muntami discourse in Mohammad Hasan Alwan’s 2011, Alqundus – The Beaver. The hero suffers from searching for his lost self and resisting the feeling of laziness that has resulted from his meaningless life. The study aims at monitoring and analysing the framework of paradox in the novel’s discourse through the artistic analysis approach. This is show how powerful the style of paradox is in disclosing life’s contradictions, answering existential questions, and calling for deeper thinking and analysis.